Police and the prosecutor's effort on supervision social help during the covid-19 pandemic - Budi S.H. Bahreisy; Yusrizal Hasbi; Zulkifli S.H.,M.H.; Hadi Iskandar; Ferdy Saputra; Romi Asmara (Geuthèë Institute, Aceh, 2023)
The condition of the Covid-19 pandemic requires the country to focus more on the protection of citizens, especially regarding the use of social assistance. Meanwhile, supervision of the distribution of social assistance funds is very important to be improved in order to avoid various practices of irregularities that open loopholes for corruption. The research used in this research is juridical empirical. The results of research related to the supervision of social assistance carried out by the police and the prosecutor's office in this supervision continue to conduct monitoring/monitoring as a form of prevention. Legal counseling and information were carried out in terms of the use of Covid-19 funds as well as the right targeted social assistance distribution mechanism. The next step is to continuously coordinate between stakeholders. The next step is to continuously coordinate between stakeholders. The implication of this research is that cooperation, coordination and harmonization between the central government, regional governments and private institutions are needed to be right on target, effective and efficient and supported by a good, integrated, transparent and accountable system in the distribution of social assistance. There has not been an accurate record of recipients of social assistance, so the monitoring process by both the National Police and the Attorney General's Office is not running optimally. Furthermore, there is still a lack of local government transparency regarding social assistance.